Potent Inhibition of Human Cytochrome P450 3A4 by Biflavone Components from Ginkgo Biloba and Selaginella Tamariscina - Wang, Bo; Shi, Chao; Feng, Lei; Pan, Wei; Tian, Xiang-Ge; Sun, Cheng-Peng; Wang, Chao; Ning, Jing; Lv, Xia; Wang, Yan; Yuan, Qian-Hui; Guan, Rui-Xuan; et al. (Frontiers in Pharmacology, 2022)
CYP3A4-mediated Phase I biotransformation is the rate-limiting step of elimination for many commonly used clinically agents. The modulatory effects of herbal medicines on CYP3A4 activity are one of the risk factors affecting the safe use of drug and herbal medicine. In the present study, the inhibitory effects of nearly hundred kinds of herbal medicines against CYP3A4 were evaluated based on a visual high-throughput screening method. Furthermore, biflavone components including bilobetin (7-demethylginkgetin, DGK), ginkgetin (GK), isoginkgetin (IGK) and amentoflavone (AMF) were identified as the main inhibitory components of Ginkgo biloba L. (GB) and Selaginella tamariscina (P. Beauv.) Spring (ST), which displayed very strong inhibitory effects toward CYP3A4. The inhibitory effects of these biflavones on clinical drugs that mainly undergo CYP3A4-dependent metabolism were evaluated. The IC50 of GK toward tamoxifen, gefitinib and ticagrelor were found to be of 0.478 ± 0.003, 0.869 ± 0.001 and 1.61 ± 0.039 μM, respectively. These results suggest potential pharmacokinetic interactions between the identified biflavones and clinical drugs undergoing CYP3A4-mediated biotransformation. The obtained information is important for guiding the rational use of herbal medicine in combination with synthetic pharmaceuticals.